ڈپریشن کی وجوہات اور حل : اسلامی تعلیمات کی روشنی میں ایک مطالعہCauses of Depression and Its Remedy: A Study in the Light of Islamic Teachings (Al-Qamar, 2022)
Man suffers from mental illness due to various reasons. One of them is depression. Contemporary man suffers from depression. Many efforts have been made since ancient times to resolve this issue. In short, we can divide these efforts into three levels. The comprehensiveness of Islam is that, it regulates the welfare of body and soul of human. This research paper discusses this issue in detail. Various causes of this issue, has been mentioned in the Qur'an and Sunnah. The Muslim philosophers, medical expert of golden era had discussed this in detail.  This paper presents an overview of the cause, its solution with accordance to the causes. The main causes of this issue are found in human nature. As man practice wrong. And deviate from Allah commands. This creates depression. How man can bear this?  And make a sound mental health. These are discussed in Islamic perspectives.
Keywords: Depression; Causes; Islamic principles